Figure and ground: an English view of the conservation of historic public spaces - Nigel Walter (Ochrona Dziedzictwa Kulturowego, 2023)
This paper considers some aspects of the way historic public space is understood in England, drawing on a selection of relevant guidance and research published by Historic England. This builds a picture of how public spaces are dealt with in official heritage publications in England, and how this relates to international discussion, particularly the Historic Urban Landscape (HUL) approach. This is followed by some reflections on figure-ground mapping, which leads to a brief discussion of the “Townscape” campaign of The Architectural Review. The paper concludes with reflections on the implications for conservation arising from broader perception of city as cultural landscape.